Weight Bias: Examining Achalasia Therapy in the Obese Patient. Issue 9 (September 2022) - Rhie, Ryan Y.; Chamblee, Dakota; Walker, Savannah; Mehaffey, Niall; Jenkins, Haley; Kutcher, Matthew E.; Moremen, Jacob
We hypothesize that obesity is a common diagnosis in those with achalasia at our institution but time to diagnosis and treatment is longer compared to normal weight counterparts due to implicit bias. We retrospectively reviewed all adult patients between 1/1/2013 and 6/31/2020 with a diagnosis of achalasia. Demographics, comorbidities, Eckardt scores, interventions, complications, time to consult, duration of symptoms, and follow-up were evaluated. More than half of the patients were seen in the most recent 2 years following POEM introduction and 138 had available BMI data. 46 were obese (33%) and 92 were non-obese (67%). Obese patients reported a shorter duration of symptoms prior to seeking treatment 12 versus 24 months. There was no difference in time to intervention or procedure offered. There was a non-significant trend toward higher leak (11 vs 5%) and overall complication rate (19 vs 17%) in obese patients. In follow-up 98 patients had BMI data. There was a a significant difference in mean BMI change -1.2 +/- 4.2 kg/m 2 in obese patients and +0.1 +/- 2.1 kg/m 2 in normal weight patients. One year follow-up was available in 16 (47%) obese and 25 (33%) non-obese patients and showed a non-significant trend toward greater weight gain in the normal/overweight group (+3.2 +/- 1.1 kg/m 2 ) compared to obese (+2.0 +/- 3.5 kg/m 2 ). Obese patients with achalasia have unique considerations. Duration of symptoms may be shorter in the obese patient with esophageal dysphagia. We noted trends toward greater weight gain following interventions in non-obese patients with equivalent complication rates